Distribution and Viability of Peripheral Blood Mononuclear Cells from Imatinib-resistant Chronic Myeloid Leukemia Patients: an In Vitro Study - Ramadhanti, Julia; Utami, Kharima Dwi; Bashari, Muhammad Hasan; Wijaya, Indra (Indonesian Society for Cancer Chemoprevention, 2023)
The incidence of Chronic Myeloid Leukemia (CML) in the world is approximately 1.5 cases per 100,000 individuals. The level of resistance to CML treatment, imatinib in Indonesia is relatively high compared to Europe. Culturing CML cells can be used as a model for the determination of pathogenesis of CML, drug efficacy testing, and drug resistance testing. Studies using CML patients’ cells to be cultured in vitro and the methods used are rarely varied. This study aims to examine the distribution and viability of peripheral blood mononuclear cells from imatinib-resistant CML patients, expected to be a reference for mononuclear cell cultures from CML patients. This study was conducted in June-August 2019 using quantitative descriptive methods. The sample was mononuclear cells isolated from peripheral blood of three imatinib-resistant CML patients at the Hemato-Oncology Polyclinic of Hasan Sadikin Hospital, each of which was cultured in vitro using RPMI 1640 for 28 days. Distribution were seen using Giemsa staining, while viability was calculated using trypan blue. Data is processed using Microsoft Excel 2013 and Graphpad. Cell viability decreased during culture. Cell distribution had a different development pattern. Blast cells, eosinophils and basophils had presentation of between 0-5%. The percentage of lymphocyte changed between 11-31%. The percentage of neutrophil changed between 16-41%. The percentage of immature cells decreased, whereas the percentage of monocyte increased. In conclusion, cell viability decreases during the culture. Distribution of cells similar to the initial condition lasted until the 7th day and in the final phase it was only dominated by monocytes.Keywords: myeloid leukemia, chronic, cell culture, in vitro, peripheral blood mononuclear cell, cell viability.